A Vermiform Appendix Herniation Presenting in an Inguinal Hernia: A Case Report from Saudi Arabia - Almutairi, Ayed; Albugami, Shoag; Alrawaji, Fatma (International Journal of Innovative Research in Medical Science, 2023)
We present a case of a 20-year-old Saudi male, who presented to the emergency room because of swelling in the right inguinal area for 3 days after getting upper respiratory tract infection, US was done in the ER and showed uncomplicated right inguinal hernia. The patient was referred to General surgery clinic. Vital signs on the clinic were normal. Abdominal examination revealed soft and lax with right reducible inguinal hernia. Preoperative laboratory test came out within the normal ranges. A routine open right inguinal hernia repair with mesh was done, incidental finding of tubular structure inferio-lateral to the hernia sac and adherent to it was identified, diagnostic laparoscopy was done which showed appendix protruding through the internal inguinal ring and laparoscopic appendectomy done. Histopathology of the hernia sac and content was appendix consistent with Amynda’s hernia